High School Students’ Perception of TV Vs Internet Advertising: A Study from The Tri-City Agglomeration (Gdańsk, Sopot, Gdynia), Poland - Piotr Oskar CZECHOWSKI; Konrad HRYNIEWICZ; Tomasz OWCZAREK; Marzena WANAGOS (Communications of International Proceedings, 2022)
The article aims to present the perception of television and Internet advertising by young people. The article shows the problems how the development of technology changes the profile of advertising recipients. In the literature on the subject, there are no studies that show that advertising has become something so common that it has ceased to be badly received by recipients. This is especially true of young consumers. In order to verify such a hypothesis, for the purposes of this article, direct research was carried out using the diagnostic survey method in the form of a questionnaire. Research conducted on 824 people among 16-19-year-olds in the period from March to June 2022. The main research problems undertaken in this study focused on whether young people positively perceive communication through television and Internet advertising? In which of them do they see more negative elements? Which of these two forms of advertising do they see more often? Based on the conducted research, it can be unequivocally stated that advertising does not lose its popularity in the surveyed group. Young people have a positive attitude towards advertising. They value artistic values and creativity. They receive messages mainly through mobile devices, which is why they see online ads more often. Television is watched sporadically, so the importance of this advertisement among 16-19-year-olds is much less. Advertising has become something that "just is" for them. They perceive it as a positive element of the reality that surrounds them. They do not associate advertising negatively as an intrusive form of information.
Keywords: advertising; young people; online advertising and TV